EFFECT OF CIDR AND PGF 2cx TO AUGMENT FERTILITY IN REPEAT BREEDING HOLSTEIN FRIESIAN CROSSBRED COWS - VIJAYARAJAN, A; MEENAKSHISUNDARAM, S (The Indian Journal of Animal Reproduction, 2023)
The aim of this study was to evaluate the effect of CIDR and PGF2a to improve the conception rate in repeatbreeding Holstein Friesian crossbred cows under field condition. The study was conducted on 56 Holstein Friesiancrossbred cows. The selected animals were divided into group I (n=28) and group 11 (n=28). Group I animals wereserved as control and were inseminated during natural estrus and animals in group II were treated with an intravaginalP4 device (CIDR) for 9 days and PGF2a was given intramuscularly 24 hrs prior to CIDR removal. Fixed time Artificialinsemination was carried out at48 and 72 hrs after CIDR removal. The overall conception rates obtained was 25per cent in group I animals and 60.71 percent in group II animals treated with CIDR and PGF2alpha.
Keywords: Cl DR; PGF 2alpha; Crossbred Cows; Repeat breeder; Conception Rate